Understanding Followers Feedback in TikTok Videos: A Netnographic Analysis on English Learning Content - Mayaputri, Velmi; Wahyuningsih (The Indonesian Institute of Science and Technology Research, 2025)
The growth of social media advances breaking the limited access of English learning experience. One of the massive users of social media currently is the TikTok application. This study examined followers’ feedback on the English learning content created by @kadang.sokinggris TikTok account. The English learning content presented by this account consists of vocabulary mastery, pronunciation, English version, and word differences. His teaching method is